Avaliação da qualidade do sono e níveis séricos de serotonina e cortisol em pacientes com dor crônica - Mesquita, Lays Fernandes (2023)
Chronic pain can affect individuals of any age and is attributed to increased morbidity, cognitive decline and immobility. In patients with chronic pain, there are important changes in neurotransmission, in addition to stress-related endocrine changes. Furthermore, poor sleep quality leads to cognitive changes, irritability and fatigue during the day and is commonly present in these patients. Thus, the present study evaluated, through the application of assistance to adult individuals diagnosed with chronic pain, treated at a rheumatology outpatient clinic in the micro-region of Alfenas-MG, the quality of life, the pattern of pain, the sleep quality, as well as serum levels of serotonin and cortisol. From the sample of 57 patients, most were women (91.2%) and aged over 40 years (87.7%). The main diagnoses involved were fibromyalgia (35%), osteoarthritis (21%) and rheumatoid arthritis (14%). The results obtained pointed to intense pain intensity and interference from external activities, regular general health status and poor sleep quality in these individuals. According to the data, there was no statistically significant correlation, neither between pain severity and sleep quality, nor between pain severity and general health status. On the other hand, there was a positive modulation of pain severity on the interference with motor activities, and a negative modulation of pain severity on the individual's mental health. It was also clear that the interference of pain in professional activities has an impact on mental health. It was not possible to verify a relationship between poor sleep quality and greater pain intensity, but there was a relevant correlation between sleep quality and mental health, also significantly impacting the general health state. The sleep quality also had an impact on daily activities and decreased mental health. Finally, in the present study, no relevant correlation was found between the diagnosis of chronic pain and changes in serum levels of serotonin and cortisol. In conclusion, the findings demonstrate the complexity of treating patients with chronic pain. Considering that chronic pain triggers a wide spectrum of organic and cognitive changes, it is essential to understand how these changes are associated, so that preventive approaches and more effective treatments may be developed.